KẾT QUẢ XỬ LÝ BƯỚC ĐẦU SỐ LIỆU ĐO SÂU TỪ TELUA TUYẾN HÒA BÌNH - THÁI NGUYÊN VÀ TUYẾN THANH HÓA - HÀ TÂY - Minh, Lê Huy; Toàn, Đinh Văn; Sơn, Võ Thanh; Thắng, Nguyễn Chiến; Duẩn, Nguyễn Bá; Thành, Nguyễn Hà; Thanh, Lê Trường; MARQUIS, GUY (Vietnam Journal of Earth Sciences, 2011)
Preliminary results of processing the sounding magnetotelluric data of Hoa Binh - Thai Nguyen and Thanh Hoa - Ha Tay profiles Two magnetotelluric surveys from Hoa Binh (HB) to Thai Nguyen (TN) and from Thanh Hoa (TH) to Ha Tay (HT) have been carried out. The lengths of these profiles are about more than 120 km with 33 stations (HB-TN), and with 31 stations (TH-HT). The geoelectrical cross-sections along two profiles obtained by two-dimensional inversion of the magnetotelluric data, recording interval ranges from 10-3 to 103 s are presented. It is shown that the main faults such as Muong La-Bac Yen, Red River, Chay River and Lo River on the HB-TN profile; Ma River, Son La and Kim Boi on the THHT one, could be recognized by rapid resistivity changes in the crust resistivity models. They are all trans-crustal deep faults with the vertical or nearly vertical dip. Assuming the Earth crust of three layers: upper, middle and lower with the depths of about 1-4km, 14-17km and 30-37km, respectively, from the seismic exploration data, the 1D geoelectrical models are obtained by using the MT software. It is shown that the middle crust’s resistivity is significantly higher than the lower and upper one, but the each layer is not homogeneous conductively. The resistivity decreases clearly in the active fault (Red River, Chat River Lo River…) zones, which could be related to the metamorphism releasing heats and fluids or upwelling of the mantle.